Development Of A Smart Fire Fighting Robot Based On Arduino Uno With A Fire Detection System And Hybrid Manual-Automatic Control - Fadhilatun Akhsan; Ali Rosyiqin; M Heru Pratama Putra; Anggi Fajar Masurogo; Tateng Sukendar (CV. AFDIFAL MAJU BERKAH, 2026)
Fire is one of the disasters that can cause material losses and casualties if not handled quickly. This study aims to design and develop a Smart Fire Fighting Robot based on Arduino Uno with a fire detection system and hybrid manual-automatic control. The system uses flame sensors to detect fire sources, an infrared temperature sensor for heat validation, DC motors for movement, a servo motor to direct the nozzle, and a water pump for extinguishing. The robot can operate in automatic mode to detect, approach, and extinguish fire autonomously, as well as in manual mode controlled via Bluetooth to improve operational flexibility. The test results show that the system is able to detect fire accurately, navigate toward the fire source, and extinguish fire effectively in small-scale fire simulations. This system is expected to support fire mitigation efforts and reduce risks to humans during emergency situations.